A European carbon border tax: Much pain, little gain - Georg Zachmann; Ben McWilliams (Bruegel, 2020)
The European Green Deal has set a target of reducing European Union carbon emissions by about 40 percent over the next ten years. Reaching this target is likely to involve a significant increase in carbon prices. Theoretically, higher carbon prices can lead to carbon leakage, or the relocation of industrial activity and its accompanying emissions out of economies with high carbon prices and into economies with low carbon prices. To address this perceived threat, the European Commission will consider the inclusion of a carbon border adjustment mechanism within the European Green Deal. This will apply a charge on goods imported into the EU, based on the emissions emitted during their production. The European Commission should not make the implementation of a carbon border adjustment mechanism into a must-have element of its climate policy. There is little in the way of strong empirical evidence that would justify a carbon-adjustment measure. Assessments of current carbon pricing schemes typically find no leakage, while ex-ante modelling tends to find limited leakage, with results highly sensitive to underlying assumptions. Energy price differentials - a proxy for carbon prices do not necessarily result in a relocation of energy-intensive production. Furthermore, significant logistical, legal and political challenges will arise during the design of a carbon border mechanism. Choices would have to be made between more efficient but highly complex and politically risky approaches, and mainly symbolic but more easily implementable solutions. To simplify the design of a carbon border mechanism whilst maximising its benefits, the Commission has proposed focusing only on carbon-intensive and trade-exposed sectors. But it will be difficult to draw a strict line between covered and non-covered sectors. Trade deviation will potentially lead to lobbying and the temptation for "cascading protectionism", with tariffs extended to industries further along value chains. A strategy of tying future climate policy to the implementation of a border adjustment mechanism might therefore hinder rather than help EU climate policy. The EU should instead focus upon the implementation of measures to trigger the development of a competitive low-carbon industry in Europe.
Keywords: 330